A method for measuring satisfaction of users of digital libraries: a case study with engineering faculty - Cendón, Beatriz Valadares; Almeida Souza, Juliana Lopes de (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
This research study proposes an instrument and a method for measuring the satisfaction of users of digital libraries of e-journals. The satisfaction questionnaire has questions on an eight point Lickert Scale about the various factors, which affect the satisfaction of the user of the digital library. These questions which were fundamented on user studies of digital libraries, on the literature of computer science and administration of information systems, included general questions on the satisfaction of the users; and satisfaction with specific aspects of the quality and the content of the system. Satisfaction with the quality of the system included questions on the search resources, the usability (ease of use, flexibility. readability, organization of information and sequence of the screens), and the access to the system (ease of access and speed). Satisfaction with the contents of the system included questions about the number of journals, their quality, their relevance, chronological coverage, up-todatedness, reliability and availability of full text). A method was developed, adapted from Bailey e Pearson (1983), who defined satisfaction as the sum of the user’s, positive or negative reaction to a set of factors. The method not only makes it easier to compare satisfaction among different areas of knowledge or among different categories of factors but also allows the normalization of results to neutralize the impact to null responses. The method was demonstrated verifying the degree of satisfaction of engineering faculty who were users of the Brazilian Capes Portal of E-Journals. The population studied came from 17 federal universities from all 5 geographic regions of Brazil. Data was collected by mean of a web-survey answered by 544 engineering faculty. Further research and improvements in the method proposed are suggested.